Soundness: Soundness of reduction with respect to denotational semantics
module plfa.part3.Soundness where
Introduction
In this chapter we prove that the reduction semantics is sound with respect to the denotational semantics, i.e., for any term L
L —↠ ƛ N implies ℰ L ≃ ℰ (ƛ N)
The proof is by induction on the reduction sequence, so the main lemma concerns a single reduction step. We prove that if any term M
steps to a term N
, then M
and N
are denotationally equal. We shall prove each direction of this if-and-only-if separately. One direction will look just like a type preservation proof. The other direction is like proving type preservation for reduction going in reverse. Recall that type preservation is sometimes called subject reduction. Preservation in reverse is a well-known property and is called subject expansion. It is also well-known that subject expansion is false for most typed lambda calculi!
Imports
open import Relation.Binary.PropositionalEquality using (_≡_; _≢_; refl; sym) open import Data.Product.Base using (_×_; Σ; Σ-syntax; ∃; ∃-syntax; proj₁; proj₂) renaming (_,_ to ⟨_,_⟩) open import Relation.Nullary.Negation using (¬_; contradiction) open import Relation.Nullary.Decidable using (Dec; yes; no) open import Function.Base using (_∘_) open import plfa.part2.Untyped using (Context; _,_; _∋_; _⊢_; ★; Z; S_; `_; ƛ_; _·_; subst; _[_]; subst-zero; ext; rename; exts; _—→_; ξ₁; ξ₂; β; ζ; _—↠_; _—→⟨_⟩_; _∎) open import plfa.part2.Substitution using (Rename; Subst; ids) open import plfa.part3.Denotational using (Value; ⊥; Env; _⊢_↓_; _`,_; _⊑_; _`⊑_; `⊥; _`⊔_; init; last; init-last; ⊑-refl; ⊑-trans; `⊑-refl; ⊑-env; ⊑-env-conj-R1; ⊑-env-conj-R2; up-env; var; ↦-elim; ↦-intro; ⊥-intro; ⊔-intro; sub; rename-pres; ℰ; _≃_; ≃-trans) open import plfa.part3.Compositional using (lambda-inversion; var-inv)
Forward reduction preserves denotations
The proof of preservation in this section mixes techniques from previous chapters. Like the proof of preservation for the STLC, we are preserving a relation defined separately from the syntax, in contrast to the intrinsically-typed terms. On the other hand, we are using de Bruijn indices for variables.
The outline of the proof remains the same in that we must prove lemmas concerning all of the auxiliary functions used in the reduction relation: substitution, renaming, and extension.
Simultaneous substitution preserves denotations
Our next goal is to prove that simultaneous substitution preserves meaning. That is, if M
results in v
in environment γ
, then applying a substitution σ
to M
gives us a program that also results in v
, but in an environment δ
in which, for every variable x
, σ x
results in the same value as the one for x
in the original environment γ
. We write δ `⊢ σ ↓ γ
for this condition.
infix 3 _`⊢_↓_ _`⊢_↓_ : ∀{Δ Γ} → Env Δ → Subst Γ Δ → Env Γ → Set _`⊢_↓_ {Δ}{Γ} δ σ γ = (∀ (x : Γ ∋ ★) → δ ⊢ σ x ↓ γ x)
As usual, to prepare for lambda abstraction, we prove an extension lemma. It says that applying the exts
function to a substitution produces a new substitution that maps variables to terms that when evaluated in δ , v
produce the values in γ , v
.
subst-ext : ∀ {Γ Δ v} {γ : Env Γ} {δ : Env Δ} → (σ : Subst Γ Δ) → δ `⊢ σ ↓ γ -------------------------- → δ `, v `⊢ exts σ ↓ γ `, v subst-ext σ d Z = var subst-ext σ d (S x′) = rename-pres S_ (λ _ → ⊑-refl) (d x′)
The proof is by cases on the de Bruijn index x
.
If it is
Z
, then we need to show thatδ , v ⊢ # 0 ↓ v
, which we have by rulevar
.If it is
S x′
,then we need to show thatδ , v ⊢ rename S_ (σ x′) ↓ γ x′
, which we obtain by therename-pres
lemma.
With the extension lemma in hand, the proof that simultaneous substitution preserves meaning is straightforward. Let’s dive in!
subst-pres : ∀ {Γ Δ v} {γ : Env Γ} {δ : Env Δ} {M : Γ ⊢ ★} → (σ : Subst Γ Δ) → δ `⊢ σ ↓ γ → γ ⊢ M ↓ v ------------------ → δ ⊢ subst σ M ↓ v subst-pres σ s (var {x = x}) = s x subst-pres σ s (↦-elim d₁ d₂) = ↦-elim (subst-pres σ s d₁) (subst-pres σ s d₂) subst-pres σ s (↦-intro d) = ↦-intro (subst-pres (λ {A} → exts σ) (subst-ext σ s) d) subst-pres σ s ⊥-intro = ⊥-intro subst-pres σ s (⊔-intro d₁ d₂) = ⊔-intro (subst-pres σ s d₁) (subst-pres σ s d₂) subst-pres σ s (sub d lt) = sub (subst-pres σ s d) lt
The proof is by induction on the semantics of M
. The two interesting cases are for variables and lambda abstractions.
For a variable
x
, we have thatv = γ x
and we need to show thatδ ⊢ σ x ↓ v
. From the premise applied tox
, we have thatδ ⊢ σ x ↓ γ x
akaδ ⊢ σ x ↓ v
.For a lambda abstraction, we must extend the substitution for the induction hypothesis. We apply the
subst-ext
lemma to show that the extended substitution maps variables to terms that result in the appropriate values.
Single substitution preserves denotations
For β reduction, (ƛ N) · M —→ N [ M ]
, we need to show that the semantics is preserved when substituting M
for de Bruijn index 0 in term N
. By inversion on the rules ↦-elim
and ↦-intro
, we have that γ , v ⊢ M ↓ w
and γ ⊢ N ↓ v
. So we need to show that γ ⊢ M [ N ] ↓ w
, or equivalently, that γ ⊢ subst (subst-zero N) M ↓ w
.
substitution : ∀ {Γ} {γ : Env Γ} {N M v w} → γ `, v ⊢ N ↓ w → γ ⊢ M ↓ v --------------- → γ ⊢ N [ M ] ↓ w substitution{Γ}{γ}{N}{M}{v}{w} dn dm = subst-pres (subst-zero M) sub-z-ok dn where sub-z-ok : γ `⊢ subst-zero M ↓ (γ `, v) sub-z-ok Z = dm sub-z-ok (S x) = var
This result is a corollary of the lemma for simultaneous substitution. To use the lemma, we just need to show that subst-zero M
maps variables to terms that produces the same values as those in γ , v
. Let y
be an arbitrary variable (de Bruijn index).
If it is
Z
, then(subst-zero M) y = M
and(γ , v) y = v
. By the premise we conclude thatγ ⊢ M ↓ v
.If it is
S x
, then(subst-zero M) (S x) = x
and(γ , v) (S x) = γ x
. So we conclude thatγ ⊢ x ↓ γ x
by rulevar
.
Reduction preserves denotations
With the substitution lemma in hand, it is straightforward to prove that reduction preserves denotations.
preserve : ∀ {Γ} {γ : Env Γ} {M N v} → γ ⊢ M ↓ v → M —→ N ---------- → γ ⊢ N ↓ v preserve (var) () preserve (↦-elim d₁ d₂) (ξ₁ r) = ↦-elim (preserve d₁ r) d₂ preserve (↦-elim d₁ d₂) (ξ₂ r) = ↦-elim d₁ (preserve d₂ r) preserve (↦-elim d₁ d₂) β = substitution (lambda-inversion d₁) d₂ preserve (↦-intro d) (ζ r) = ↦-intro (preserve d r) preserve ⊥-intro r = ⊥-intro preserve (⊔-intro d d₁) r = ⊔-intro (preserve d r) (preserve d₁ r) preserve (sub d lt) r = sub (preserve d r) lt
We proceed by induction on the semantics of M
with case analysis on the reduction.
If
M
is a variable, then there is no such reduction.If
M
is an application, then the reduction is either a congruence (ξ₁ or ξ₂) or β. For each congruence, we use the induction hypothesis. For β reduction we use the substitution lemma and thesub
rule.The rest of the cases are straightforward.
Reduction reflects denotations
This section proves that reduction reflects the denotation of a term. That is, if N
results in v
, and if M
reduces to N
, then M
also results in v
. While there are some broad similarities between this proof and the above proof of semantic preservation, we shall require a few more technical lemmas to obtain this result.
The main challenge is dealing with the substitution in β reduction:
(ƛ N) · M —→ N [ M ]
We have that γ ⊢ N [ M ] ↓ v
and need to show that γ ⊢ (ƛ N) · M ↓ v
. Now consider the derivation of γ ⊢ N [ M ] ↓ v
. The term M
may occur 0, 1, or many times inside N [ M ]
. At each of those occurrences, M
may result in a different value. But to build a derivation for (ƛ N) · M
, we need a single value for M
. If M
occurred more than 1 time, then we can join all of the different values using ⊔
. If M
occurred 0 times, then we do not need any information about M
and can therefore use ⊥
for the value of M
.
Renaming reflects meaning
Previously we showed that renaming variables preserves meaning. Now we prove the opposite, that it reflects meaning. That is, if δ ⊢ rename ρ M ↓ v
, then γ ⊢ M ↓ v
, where (δ ∘ ρ) `⊑ γ
.
ext-`⊑ : ∀ {Γ Δ v} {γ : Env Γ} {δ : Env Δ} → (ρ : Rename Γ Δ) → (δ ∘ ρ) `⊑ γ ------------------------------ → ((δ `, v) ∘ ext ρ) `⊑ (γ `, v) ext-`⊑ ρ lt Z = ⊑-refl ext-`⊑ ρ lt (S x) = lt xThe proof is then as follows.
rename-reflect : ∀ {Γ Δ v} {γ : Env Γ} {δ : Env Δ} { M : Γ ⊢ ★} → {ρ : Rename Γ Δ} → (δ ∘ ρ) `⊑ γ → δ ⊢ rename ρ M ↓ v ------------------------------------ → γ ⊢ M ↓ v rename-reflect {M = ` x} all-n d with var-inv d ... | lt = sub var (⊑-trans lt (all-n x)) rename-reflect {M = ƛ N}{ρ = ρ} all-n (↦-intro d) = ↦-intro (rename-reflect (ext-`⊑ ρ all-n) d) rename-reflect {M = ƛ N} all-n ⊥-intro = ⊥-intro rename-reflect {M = ƛ N} all-n (⊔-intro d₁ d₂) = ⊔-intro (rename-reflect all-n d₁) (rename-reflect all-n d₂) rename-reflect {M = ƛ N} all-n (sub d₁ lt) = sub (rename-reflect all-n d₁) lt rename-reflect {M = L · M} all-n (↦-elim d₁ d₂) = ↦-elim (rename-reflect all-n d₁) (rename-reflect all-n d₂) rename-reflect {M = L · M} all-n ⊥-intro = ⊥-intro rename-reflect {M = L · M} all-n (⊔-intro d₁ d₂) = ⊔-intro (rename-reflect all-n d₁) (rename-reflect all-n d₂) rename-reflect {M = L · M} all-n (sub d₁ lt) = sub (rename-reflect all-n d₁) lt
We cannot prove this lemma by induction on the derivation of δ ⊢ rename ρ M ↓ v
, so instead we proceed by induction on M
.
If it is a variable, we apply the inversion lemma to obtain that
v ⊑ δ (ρ x)
. Instantiating the premise tox
we haveδ (ρ x) ⊑ γ x
, so we conclude by thevar
rule.If it is a lambda abstraction
ƛ N
, we have renameρ (ƛ N) = ƛ (rename (ext ρ) N)
. We proceed by cases onδ ⊢ ƛ (rename (ext ρ) N) ↓ v
.Rule
↦-intro
: To satisfy the premise of the induction hypothesis, we prove that the renaming can be extended to be a mapping fromγ , v
toδ , v
.Rule
⊥-intro
: We simply apply⊥-intro
.Rule
⊔-intro
: We apply the induction hypotheses and⊔-intro
.Rule
sub
: We apply the induction hypothesis andsub
.
If it is an application
L · M
, we haverename ρ (L · M) = (rename ρ L) · (rename ρ M)
. We proceed by cases onδ ⊢ (rename ρ L) · (rename ρ M) ↓ v
and all the cases are straightforward.
In the upcoming uses of rename-reflect
, the renaming will always be the increment function. So we prove a corollary for that special case.
rename-inc-reflect : ∀ {Γ v′ v} {γ : Env Γ} { M : Γ ⊢ ★} → (γ `, v′) ⊢ rename S_ M ↓ v ---------------------------- → γ ⊢ M ↓ v rename-inc-reflect d = rename-reflect `⊑-refl d
Substitution reflects denotations, the variable case
We are almost ready to begin proving that simultaneous substitution reflects denotations. That is, if γ ⊢ (subst σ M) ↓ v
, then γ ⊢ σ k ↓ δ k
and δ ⊢ M ↓ v
for any k
and some δ
. We shall start with the case in which M
is a variable x
. So instead the premise is γ ⊢ σ x ↓ v
and we need to show that δ ⊢ ` x ↓ v
for some δ
. The δ
that we choose shall be the environment that maps x
to v
and every other variable to ⊥
.
Next we define the environment that maps x
to v
and every other variable to ⊥
, that is const-env x v
. To tell variables apart, we define the following function for deciding equality of variables.
_var≟_ : ∀ {Γ} → (x y : Γ ∋ ★) → Dec (x ≡ y) Z var≟ Z = yes refl Z var≟ (S _) = no λ() (S _) var≟ Z = no λ() (S x) var≟ (S y) with x var≟ y ... | yes refl = yes refl ... | no neq = no λ{refl → neq refl} var≟-refl : ∀ {Γ} (x : Γ ∋ ★) → (x var≟ x) ≡ yes refl var≟-refl Z = refl var≟-refl (S x) rewrite var≟-refl x = refl
Now we use var≟
to define const-env
.
const-env : ∀{Γ} → (x : Γ ∋ ★) → Value → Env Γ const-env x v y with x var≟ y ... | yes _ = v ... | no _ = ⊥
Of course, const-env x v
maps x
to value v
same-const-env : ∀{Γ} {x : Γ ∋ ★} {v} → (const-env x v) x ≡ v same-const-env {x = x} rewrite var≟-refl x = refl
and const-env x v
maps y
to ⊥
, so long as x ≢ y
.
diff-const-env : ∀{Γ} {x y : Γ ∋ ★} {v} → x ≢ y ------------------- → const-env x v y ≡ ⊥ diff-const-env {Γ} {x} {y} neq with x var≟ y ... | yes eq = contradiction eq neq ... | no _ = refl
So we choose const-env x v
for δ
and obtain δ ⊢ ` x ↓ v
with the var
rule.
It remains to prove that γ `⊢ σ ↓ δ
and δ ⊢ M ↓ v
for any k
, given that we have chosen const-env x v
for δ
. We shall have two cases to consider, x ≡ y
or x ≢ y
.
Now to finish the two cases of the proof.
- In the case where
x ≡ y
, we need to show thatγ ⊢ σ y ↓ v
, but that’s just our premise. - In the case where
x ≢ y
, we need to show thatγ ⊢ σ y ↓ ⊥
, which we do via rule⊥-intro
.
Thus, we have completed the variable case of the proof that simultaneous substitution reflects denotations. Here is the proof again, formally.
subst-reflect-var : ∀ {Γ Δ} {γ : Env Δ} {x : Γ ∋ ★} {v} {σ : Subst Γ Δ} → γ ⊢ σ x ↓ v ----------------------------------------- → Σ[ δ ∈ Env Γ ] γ `⊢ σ ↓ δ × δ ⊢ ` x ↓ v subst-reflect-var {Γ}{Δ}{γ}{x}{v}{σ} xv rewrite sym (same-const-env {Γ}{x}{v}) = ⟨ const-env x v , ⟨ const-env-ok , var ⟩ ⟩ where const-env-ok : γ `⊢ σ ↓ const-env x v const-env-ok y with x var≟ y ... | yes x≡y rewrite sym x≡y | same-const-env {Γ}{x}{v} = xv ... | no x≢y rewrite diff-const-env {Γ}{x}{y}{v} x≢y = ⊥-intro
Substitutions and environment construction
Every substitution produces terms that can evaluate to ⊥
.
subst-⊥ : ∀{Γ Δ}{γ : Env Δ}{σ : Subst Γ Δ} ----------------- → γ `⊢ σ ↓ `⊥ subst-⊥ x = ⊥-intro
If a substitution produces terms that evaluate to the values in both γ₁
and γ₂
, then those terms also evaluate to the values in γ₁ ⊔ γ₂
.
subst-⊔ : ∀{Γ Δ}{γ : Env Δ}{γ₁ γ₂ : Env Γ}{σ : Subst Γ Δ} → γ `⊢ σ ↓ γ₁ → γ `⊢ σ ↓ γ₂ ------------------------- → γ `⊢ σ ↓ (γ₁ `⊔ γ₂) subst-⊔ γ₁-ok γ₂-ok x = ⊔-intro (γ₁-ok x) (γ₂-ok x)
The Lambda constructor is injective
lambda-inj : ∀ {Γ} {M N : Γ , ★ ⊢ ★ } → _≡_ {A = Γ ⊢ ★} (ƛ M) (ƛ N) --------------------------- → M ≡ N lambda-inj refl = refl
Simultaneous substitution reflects denotations
In this section we prove a central lemma, that substitution reflects denotations. That is, if γ ⊢ subst σ M ↓ v
, then δ ⊢ M ↓ v
and γ `⊢ σ ↓ δ
for some δ
. We shall proceed by induction on the derivation of γ ⊢ subst σ M ↓ v
. This requires a minor restatement of the lemma, changing the premise to γ ⊢ L ↓ v
and L ≡ subst σ M
.
split : ∀ {Γ} {M : Γ , ★ ⊢ ★} {δ : Env (Γ , ★)} {v} → δ ⊢ M ↓ v -------------------------- → (init δ `, last δ) ⊢ M ↓ v split {δ = δ} δMv rewrite init-last δ = δMv subst-reflect : ∀ {Γ Δ} {δ : Env Δ} {M : Γ ⊢ ★} {v} {L : Δ ⊢ ★} {σ : Subst Γ Δ} → δ ⊢ L ↓ v → subst σ M ≡ L --------------------------------------- → Σ[ γ ∈ Env Γ ] δ `⊢ σ ↓ γ × γ ⊢ M ↓ v subst-reflect {M = M}{σ = σ} (var {x = y}) eqL with M ... | ` x with var {x = y} ... | yv rewrite sym eqL = subst-reflect-var {σ = σ} yv subst-reflect {M = M} (var {x = y}) () | M₁ · M₂ subst-reflect {M = M} (var {x = y}) () | ƛ M′ subst-reflect {M = M}{σ = σ} (↦-elim d₁ d₂) eqL with M ... | ` x with ↦-elim d₁ d₂ ... | d′ rewrite sym eqL = subst-reflect-var {σ = σ} d′ subst-reflect (↦-elim d₁ d₂) () | ƛ M′ subst-reflect{Γ}{Δ}{γ}{σ = σ} (↦-elim d₁ d₂) refl | M₁ · M₂ with subst-reflect {M = M₁} d₁ refl | subst-reflect {M = M₂} d₂ refl ... | ⟨ δ₁ , ⟨ subst-δ₁ , m1 ⟩ ⟩ | ⟨ δ₂ , ⟨ subst-δ₂ , m2 ⟩ ⟩ = ⟨ δ₁ `⊔ δ₂ , ⟨ subst-⊔ {γ₁ = δ₁}{γ₂ = δ₂}{σ = σ} subst-δ₁ subst-δ₂ , ↦-elim (⊑-env m1 (⊑-env-conj-R1 δ₁ δ₂)) (⊑-env m2 (⊑-env-conj-R2 δ₁ δ₂)) ⟩ ⟩ subst-reflect {M = M}{σ = σ} (↦-intro d) eqL with M ... | ` x with (↦-intro d) ... | d′ rewrite sym eqL = subst-reflect-var {σ = σ} d′ subst-reflect {σ = σ} (↦-intro d) eq | ƛ M′ with subst-reflect {σ = exts σ} d (lambda-inj eq) ... | ⟨ δ′ , ⟨ exts-σ-δ′ , m′ ⟩ ⟩ = ⟨ init δ′ , ⟨ ((λ x → rename-inc-reflect (exts-σ-δ′ (S x)))) , ↦-intro (up-env (split m′) (var-inv (exts-σ-δ′ Z))) ⟩ ⟩ subst-reflect (↦-intro d) () | M₁ · M₂ subst-reflect {σ = σ} ⊥-intro eq = ⟨ `⊥ , ⟨ subst-⊥ {σ = σ} , ⊥-intro ⟩ ⟩ subst-reflect {σ = σ} (⊔-intro d₁ d₂) eq with subst-reflect {σ = σ} d₁ eq | subst-reflect {σ = σ} d₂ eq ... | ⟨ δ₁ , ⟨ subst-δ₁ , m1 ⟩ ⟩ | ⟨ δ₂ , ⟨ subst-δ₂ , m2 ⟩ ⟩ = ⟨ δ₁ `⊔ δ₂ , ⟨ subst-⊔ {γ₁ = δ₁}{γ₂ = δ₂}{σ = σ} subst-δ₁ subst-δ₂ , ⊔-intro (⊑-env m1 (⊑-env-conj-R1 δ₁ δ₂)) (⊑-env m2 (⊑-env-conj-R2 δ₁ δ₂)) ⟩ ⟩ subst-reflect (sub d lt) eq with subst-reflect d eq ... | ⟨ δ , ⟨ subst-δ , m ⟩ ⟩ = ⟨ δ , ⟨ subst-δ , sub m lt ⟩ ⟩
Case
var
: We havesubst σ M ≡ y
, soM
must also be a variable, sayx
. We apply the lemmasubst-reflect-var
to conclude.Case
↦-elim
: We havesubst σ M ≡ L₁ · L₂
. We proceed by cases onM
.Case
M ≡ ` x
: We apply thesubst-reflect-var
lemma again to conclude.Case
M ≡ M₁ · M₂
: By the induction hypothesis, we have someδ₁
andδ₂
such thatδ₁ ⊢ M₁ ↓ v₁ ↦ v₃
andγ `⊢ σ ↓ δ₁
, as well asδ₂ ⊢ M₂ ↓ v₁
andγ `⊢ σ ↓ δ₂
. By⊑-env
we haveδ₁ ⊔ δ₂ ⊢ M₁ ↓ v₁ ↦ v₃
andδ₁ ⊔ δ₂ ⊢ M₂ ↓ v₁
(using⊑-env-conj-R1
and⊑-env-conj-R2
), and thereforeδ₁ ⊔ δ₂ ⊢ M₁ · M₂ ↓ v₃
. We conclude this case by obtainingγ `⊢ σ ↓ δ₁ ⊔ δ₂
by thesubst-⊔
lemma.
Case
↦-intro
: We havesubst σ M ≡ ƛ L′
. We proceed by cases onM
.Case
M ≡ x
: We apply thesubst-reflect-var
lemma.Case
M ≡ ƛ M′
: By the induction hypothesis, we have(δ′ , v′) ⊢ M′ ↓ v₂
and(δ , v₁) ⊢ exts σ ↓ (δ′ , v′)
. From the later we have(δ , v₁) ⊢ # 0 ↓ v′
. By the lemmavar-inv
we havev′ ⊑ v₁
, so by theup-env
lemma we have(δ′ , v₁) ⊢ M′ ↓ v₂
and thereforeδ′ ⊢ ƛ M′ ↓ v₁ → v₂
. We also need to show thatδ ⊢ σ ↓ δ′
. Fixk
. We have(δ , v₁) ⊢ rename S_ σ k ↓ δ k′
. We then apply the lemmarename-inc-reflect
to obtainδ ⊢ σ k ↓ δ k′
, so this case is complete.
Case
⊥-intro
: We choose⊥
forδ
. We have⊥ ⊢ M ↓ ⊥
by⊥-intro
. We haveδ `⊢ σ ↓ `⊥
by the lemmasubst-⊥
.Case
⊔-intro
: By the induction hypothesis we haveδ₁ ⊢ M ↓ v₁
,δ₂ ⊢ M ↓ v₂
,δ `⊢ σ ↓ δ₁
, andδ `⊢ σ ↓ δ₂
. We haveδ₁ ⊔ δ₂ ⊢ M ↓ v₁
andδ₁ ⊔ δ₂ ⊢ M ↓ v₂
by⊑-env
with⊑-env-conj-R1
and⊑-env-conj-R2
. So by⊔-intro
we haveδ₁ ⊔ δ₂ ⊢ M ↓ v₁ ⊔ v₂
. Bysubst-⊔
we conclude thatδ `⊢ σ ↓ δ₁ ⊔ δ₂
.
Single substitution reflects denotations
Most of the work is now behind us. We have proved that simultaneous substitution reflects denotations. Of course, β reduction uses single substitution, so we need a corollary that proves that single substitution reflects denotations. That is, given terms N : (Γ , ★ ⊢ ★)
and M : (Γ ⊢ ★)
, if γ ⊢ N [ M ] ↓ w
, then γ ⊢ M ↓ v
and (γ , v) ⊢ N ↓ w
for some value v
. We have N [ M ] = subst (subst-zero M) N
.
We first prove a lemma about subst-zero
, that if δ ⊢ subst-zero M ↓ γ
, then γ `⊑ (δ , w) × δ ⊢ M ↓ w
for some w
.
subst-zero-reflect : ∀ {Δ} {δ : Env Δ} {γ : Env (Δ , ★)} {M : Δ ⊢ ★} → δ `⊢ subst-zero M ↓ γ ---------------------------------------- → Σ[ w ∈ Value ] γ `⊑ (δ `, w) × δ ⊢ M ↓ w subst-zero-reflect {δ = δ} {γ = γ} δσγ = ⟨ last γ , ⟨ lemma , δσγ Z ⟩ ⟩ where lemma : γ `⊑ (δ `, last γ) lemma Z = ⊑-refl lemma (S x) = var-inv (δσγ (S x))
We choose w
to be the last value in γ
and we obtain δ ⊢ M ↓ w
by applying the premise to variable Z
. Finally, to prove γ `⊑ (δ , w)
, we prove a lemma by induction in the input variable. The base case is trivial because of our choice of w
. In the induction case, S x
, the premise δ ⊢ subst-zero M ↓ γ
gives us δ ⊢ x ↓ γ (S x)
and then using var-inv
we conclude that γ (S x) ⊑ (δ `, w) (S x)
.
Now to prove that substitution reflects denotations.
substitution-reflect : ∀ {Δ} {δ : Env Δ} {N : Δ , ★ ⊢ ★} {M : Δ ⊢ ★} {v} → δ ⊢ N [ M ] ↓ v ------------------------------------------------ → Σ[ w ∈ Value ] δ ⊢ M ↓ w × (δ `, w) ⊢ N ↓ v substitution-reflect d with subst-reflect d refl ... | ⟨ γ , ⟨ δσγ , γNv ⟩ ⟩ with subst-zero-reflect δσγ ... | ⟨ w , ⟨ ineq , δMw ⟩ ⟩ = ⟨ w , ⟨ δMw , ⊑-env γNv ineq ⟩ ⟩
We apply the subst-reflect
lemma to obtain δ ⊢ subst-zero M ↓ γ
and γ ⊢ N ↓ v
for some γ
. Using the former, the subst-zero-reflect
lemma gives us γ `⊑ (δ , w)
and δ ⊢ M ↓ w
. We conclude that δ , w ⊢ N ↓ v
by applying the ⊑-env
lemma, using γ ⊢ N ↓ v
and γ `⊑ (δ , w)
.
Reduction reflects denotations
Now that we have proved that substitution reflects denotations, we can easily prove that reduction does too.
reflect-beta : ∀{Γ}{γ : Env Γ}{M N}{v} → γ ⊢ (N [ M ]) ↓ v → γ ⊢ (ƛ N) · M ↓ v reflect-beta d with substitution-reflect d ... | ⟨ v₂′ , ⟨ d₁′ , d₂′ ⟩ ⟩ = ↦-elim (↦-intro d₂′) d₁′ reflect : ∀ {Γ} {γ : Env Γ} {M M′ N v} → γ ⊢ N ↓ v → M —→ M′ → M′ ≡ N --------------------------------- → γ ⊢ M ↓ v reflect var (ξ₁ r) () reflect var (ξ₂ r) () reflect{γ = γ} (var{x = x}) β mn with var{γ = γ}{x = x} ... | d′ rewrite sym mn = reflect-beta d′ reflect var (ζ r) () reflect (↦-elim d₁ d₂) (ξ₁ r) refl = ↦-elim (reflect d₁ r refl) d₂ reflect (↦-elim d₁ d₂) (ξ₂ r) refl = ↦-elim d₁ (reflect d₂ r refl) reflect (↦-elim d₁ d₂) β mn with ↦-elim d₁ d₂ ... | d′ rewrite sym mn = reflect-beta d′ reflect (↦-elim d₁ d₂) (ζ r) () reflect (↦-intro d) (ξ₁ r) () reflect (↦-intro d) (ξ₂ r) () reflect (↦-intro d) β mn with ↦-intro d ... | d′ rewrite sym mn = reflect-beta d′ reflect (↦-intro d) (ζ r) refl = ↦-intro (reflect d r refl) reflect ⊥-intro r mn = ⊥-intro reflect (⊔-intro d₁ d₂) r mn rewrite sym mn = ⊔-intro (reflect d₁ r refl) (reflect d₂ r refl) reflect (sub d lt) r mn = sub (reflect d r mn) lt
Reduction implies denotational equality
We have proved that reduction both preserves and reflects denotations. Thus, reduction implies denotational equality.
reduce-equal : ∀ {Γ} {M : Γ ⊢ ★} {N : Γ ⊢ ★} → M —→ N --------- → ℰ M ≃ ℰ N reduce-equal {Γ}{M}{N} r γ v = ⟨ (λ m → preserve m r) , (λ n → reflect n r refl) ⟩
We conclude with the soundness property, that multi-step reduction to a lambda abstraction implies denotational equivalence with a lambda abstraction.
soundness : ∀{Γ} {M : Γ ⊢ ★} {N : Γ , ★ ⊢ ★} → M —↠ ƛ N ----------------- → ℰ M ≃ ℰ (ƛ N) soundness (.(ƛ _) ∎) γ v = ⟨ (λ x → x) , (λ x → x) ⟩ soundness {Γ} (L —→⟨ r ⟩ M—↠N) γ v = let ih = soundness M—↠N in let e = reduce-equal r in ≃-trans {Γ} e ih γ v
Unicode
This chapter uses the following unicode:
≟ U+225F QUESTIONED EQUAL TO (\?=)